Assessing E-Government Effectiveness: A Structural Equation Modeling Approach - Ameen, Aso K.; Kadir, Dler H.; Abdullah, Dana A.; Maolood, Ismail Y.; Khidir, Hewir A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
In this study, we address the pressing need to improve e-government services by conducting a comprehensive evaluation of document management practices within the Ministry of Higher Education in the Kurdistan Region of Iraq. Employing structural equation modeling and regression modeling techniques, we assess the effectiveness of key variables using the six factors (digitalization, utility, reliability, efficiency, user satisfaction, and accessibility) under the e-government assessment model. Our findings reveal that user satisfaction and ease of access are pivotal for the success of e-government services, with digitization and efficiency significantly impacting operational effectiveness. Furthermore, it also concerns that without improving the overall user satisfaction, the level of acceptance and use of e-government remains low. High user satisfaction can make a lot of difference in overall engagement besides improving service delivery among organizations. Through insights specific to the Kurdistan Region, we underscore the importance of balancing technical infrastructure with user experience. Our proposed six-factor model offers valuable guidance for policymakers and practitioners globally, aiming to enhance e-government services.